Exercise physiology in cirrhosis and the potential benefits of exercise interventions: A review. Issue 10 (10th March 2021) - West, Jack; Gow, Paul J; Testro, Adam; Chapman, Brooke; Sinclair, Marie
Abstract: Reduction in muscle mass is a highly prevalent phenomenon in cirrhosis and is now well‐documented to be associated with significant morbidity and mortality. Research into muscle loss in cirrhosis remains limited by an ongoing poor understanding of its relationship with muscle function, physical activity, and aerobic capacity. Alterations in exercise physiology have been documented in studies of individuals with cirrhosis that provide important information on physical function that is not captured by simple quantification of muscle mass. Despite expert consensus recommending regular exercise in end‐stage liver disease to maintain muscle mass and function, there is little evidence guiding clinicians as to which form of exercise or delivery mechanism is most effective. It also remains unproven whether any specific intervention can alter clinically relevant outcomes. This review article summarizes the available literature regarding the changes in exercise physiology observed in cirrhosis, the associated impact on physical capacity, and the results of existing trials that examine the potential benefits of exercise delivery in patients with cirrhosis, particularly pertaining to their impact on exercise physiology.